UN use of private military and security companies
Although subject to little discussion, the UN has increasingly paid private military and security companies (PMSCs) for a range of services in the areas of humanitarian affairs, peacebuilding and development. However, this practice has rarely translated into coherent policies or guidelines that could guide the UN in setting standards or ensuring responsible contracting procedures. This paper explores UN demand for PMSCs and identifies the need for a more proactive, sensitive and deliberate political approach in order to avoid potential pitfalls associated with involving PMSCs in the delivery of UN tasks.